LEARNING MANAGEMENT BASED ON RELIGIOUS MODERATION - Fandrik Haris Setia Putra; Zaenol Fajri; Fadhail Nur Wahid Ramli (Raudhah - Proud To Be Professional, 2023)
Schools must use learning management for the learning process to go as intended. The principal and instructors govern the planning, supervision, assessment, and student discipline processes in schools. As a result, the instructor plays a crucial role in education so pupils can understand and learn. For pupils to be able to put the concepts of love and compassion for one another into practice, one of the instructor's responsibilities is to also teach about religious consciousness. Students are expected to be aware of God's teachings, particularly those related to obeying his commands and avoiding his prohibitions. This study describes the MI Islamiayh Situbondo's religious moderation-based learning management system. This research is qualitative, and the data collection methods are interviews, documentation, and observation. The findings demonstrated that MI Islamiyah's learning management application focuses on curriculum, teachers, students, facilities, and parents. These areas must be well-organized to ensure that learning proceeds as intended. Students are taught to be hablum minallah and habblum minannas in MI Islamiyah, and professors offer direction on what it means to be a religious person and how to deepen one's faith and piety. Children are also taught ethics toward their friends and other people. It follows that by paying attention to the issues listed above, religious moderation-based learning can be implemented..